Effect of Teaching Academic Skills on Academic Achievement in Medical Emergency Students - Otaghi M (Education Strategies in Medical Sciences, 2015)
Aims: An important aspect of the student’s learning in academic performance is self-regulating. Students without required academic achievement skills need educational approaches to obtain the required insight in self-regulate learning. The aim of this study was to determine the effects of teaching academic skills on academic achievement in the advanced diploma medical emergency students of Ilam University of Medical Sciences.